Analisi dell’anisotropia microstrutturale in materiali compositi rinforzati con fibre corte - A. Bernasconi; F. Cosmi; D. Dreossi (Fracture and Structural Integrity)
Synchrotron light microtomography has proved to be particularly efficient in order to analyze the microstructural characteristics in terms of reinforce fibre distribution and orientation in glass fibre reinforced composites. The spatial distribution of fibre within the polymeric matrix could be detected even in case of fibre characterized by a small diameter (10 micrometers average diameter). Differences in orientation distribution within a sample could be measured using the Mean Intercept Length (MIL) and the fabric tensor. The results presented herein refer to a sample of a 30% by weight glass fibre reinforced polyamide 6, extracted form a thin plate.